Urban Rail Transit - Ning, Bin; Han, Baoming; Shi, Zhongheng; Zhou, Xuesong
Urban Rail Transit is a peer-reviewed, international, interdisciplinary and open-access journal published under the SpringerOpen brand that provides a platform for scientists, researchers and engineers of urban rail transit to publish their original, significant articles on topics in urban rail transportation operation and management, design and planning, civil engineering, equipment and systems and other related topics to urban rail transit. It is to promote the academic discussions and technical exchanges among peers in the field. The journal also reports important news on the development and operating experience of urban rail transit and related government policies, laws, guidelines, and regulations. It could serve as an important reference for decision¬makers and technologists in urban rail research and construction field.     Specific topics cover: Column I: Urban Rail Transportation Operation and Management • urban rail transit flow theory, operation, planning, control and management • traffic and transport safety   • traffic polices and economics      • urban rail management  • traffic information management                     • urban rail scheduling • train scheduling and management  • strategies of ticket price         • traffic information engineering & control    • intelligent transportation system (ITS) and information technology     • economics, finance, business & industry  • train operation, control    • transport Industries   • transportation engineering     Column II: Urban Rail Transportation Design and Planning • urban rail planning   • pedestrian studies     • sustainable transport engineering   • rail electrification     • rail signaling and communication   • Intelligent & Automated Transport System Technology               • rolling stock design theory and structural reliability      • urban rail transit electrification and automation technologies              • transport Industries                                    • transportation engineering    Column III: Civil Engineering • civil engineering technologies • maintenance of rail infrastructure • transportation infrastructure systems • roads, bridges, tunnels, and underground engineering              • subgrade and pavement maintenance and performance    Column IV: Equipments and Systems • mechanical-electronic technologies  • manufacturing engineering                                         • inspection for trains and rail • vehicle-track coupling system dynamics, simulation and control          • superconductivity and levitation technology • magnetic suspension and evacuated tube transport   • railway technology & engineering    • Railway Transport  Industries    • transport & vehicle engineering    Column V: other topics of interest    • modern tram                           • interdisciplinary transportation research  • environmental impacts such as vibration, noise and pollution    Article types: • Papers. Reports of original research work. • Design notes. Brief contributions on current design, development and application work; not normally more than 2500 words (3 journal pages), including descriptions of apparatus or techniques developed for a specific purpose, important experimental or theoretical points and novel technical solutions to commonly encountered problems. • Rapid communications. Brief, urgent announcements of significant advances or preliminary accounts of new work, not more than 3500 words (4 journal pages). The most important criteria for acceptance of a rapid communication are novel and significant. For these articles authors must state briefly, in a covering letter, exactly why their works merit rapid publication. • Review articles. These are intended to summarize accepted practice and report on recent progress in selected areas. Such articles are generally commissioned from experts in various field s by the Editorial Board, but others wishing to write a review article may submit an outline for preliminary consideration.